Z dziejów czasopisma „Вестник Европы” („Rok Izmajłowa”) . - Dąbrowska, Magdalena (Przegląd Rusycystyczny, 2011)
К ИСТОРИИ ЖУРНАЛА „ВЕСТНИК ЕВРОПЫ” („ГОД ИЗМАЙЛОВА”) Резюме Журнал „Вестник Европы” основан в 1802 году Н.М. Карамзиным. Потом его история связана с разными издателями: в 1814 году с Владимиром Измайловым (1773–1830) — сентименталистом, прозаиком, поэтом, литературным критиком, переводчиком. Он является также издателем журналов „Патриот” (1804) и „Российский музеум” (1815).В настоящей статье подвергаются анализу два отдела журнала: поэзия и проза. В первом в 1814 году были напечатаны, напр., стихотворения В.A. Жуковского и А.C. Пушкина, во втором — напр., повести Владимира Измайлова. В статье предпри-нята также попытка характеристики предисловия к журналу. FROM THE HISTORY OF „VESTNIK EVROPY” MAGAZINE („IZMAILOV’S YEAR”) Summary „Vestnik Evropy” magazine was set up in 1802 by N.M. Karamzin. Later, its publish-ers kept changing: in 1814 it was Vladimir Izmailov (1773–1830) — the representative of sentimentalism, prose writer, poet, literary critic and translator. Other magazines issued by him were „Patryot” (1804) and „Rossyisky muzeum” (1815).This article mainly discusses two sections of the magazine: poetry and prose. In the former, in 1814 among others compositions of V.A. Joukoffsky and A.S. Pushkin were published, while in the latter — Vladimir Izmailov’s stories. Also, the preface to the magazine is dis-cussed here.